2014
DOI: 10.1007/s00343-015-4044-7
|View full text |Cite
|
Sign up to set email alerts
|

Why does the IOD-ENSO teleconnection disappear in some decades?

Abstract: Lag correlations between sea surface temperature anomalies (SSTA) in the southeastern tropical Indian Ocean (STIO) in fall and Niño 3.4 SSTA in the eastern equatorial Pacifi c in the following fall are subjected to decadal variation, with positive correlations during some decades and negative correlations during others. Negative correlations are smaller and of shorter duration than positive correlations. Variations in lag correlations suggest that the use of the Indian Ocean Dipole (IOD) as a predictor of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The IOD-ENSO precursory teleconnection, as represented by the running mean lag correlations between the STIO SSTA in fall and the Niño3.4 SSTA in the next fall, with a running window of 11, years, undergoes obvious decadal variability (Xu and Yuan, 2014). As shown in Figure 1A, the running mean lag correlations after the 1990s are positive, consistent with the analysis of Yuan et al (2013).…”
Section: Iod-enso Precursory Teleconnection In Cmip Modelssupporting
confidence: 81%
See 2 more Smart Citations
“…The IOD-ENSO precursory teleconnection, as represented by the running mean lag correlations between the STIO SSTA in fall and the Niño3.4 SSTA in the next fall, with a running window of 11, years, undergoes obvious decadal variability (Xu and Yuan, 2014). As shown in Figure 1A, the running mean lag correlations after the 1990s are positive, consistent with the analysis of Yuan et al (2013).…”
Section: Iod-enso Precursory Teleconnection In Cmip Modelssupporting
confidence: 81%
“…Thus, the teleconnection during the negative correlation periods is believed to be different from that during the positive correlation periods. The structure and possible dynamics of the teleconnection during the negative phases of the decadal variability have been analyzed in Xu and Yuan (2014). In this study, we only focus on the positive phases for two reasons.…”
Section: Iod-enso Precursory Teleconnection In Cmip Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ohba and Ueda (2009) demonstrated that the IOBM is associated with the atmospheric mean state via modulation of heat flux at the IO surface, whereas the IOD is caused by various dynamic and thermodynamic factors through wind modulation in the equatorial IO. Decadal changes in the IOBM and IOD also reveal distinct features and mechanisms (Ding et al 2010;Xu and Yuan 2015).…”
Section: Introductionmentioning
confidence: 94%
“…The oceanic channel dynamics are evidenced by the propagation of sea level from the STIO to the western equatorial Pacific Ocean, giving rise to the significant lag correlations between the oceanic anomalies in STIO in fall and those in the Pacific equatorial vertical section and in the cold tongue at the one-year time lag (Yuan et al, 2013). Recent studies have also suggested that the IOD-ENSO teleconnection is subject to decadal and multi-decadal variations (Xu et al, 2013;Izumo et al, 2014;Xu and Yuan, 2015), the dynamics of which are not clear at present.…”
Section: Introductionmentioning
confidence: 99%